Pengalaman Para Peternak Sapi Dalam Menghadapi Wabah Penyakit Mulut Kuku (PMK) DiKecamatan Panggul Kabupaten Trenggalek - Dhea Hilda Sari; Diyah Utami (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Foot and mouth disease (FMD) is a common infectious disease among livestock farmers, affecting cloven-hoofed livestock such as goats and cattle. The current phenomenon of widespread outbreaks of FMD in cattle is a major concern. This study aims to analyze awareness and understanding, uncover and understand the essence of experiences, and analyze the actions of cattle farmers during FMD outbreaks. The method used in this study is a qualitative research type using a grounded research model, a phenomenological approach from Edmund Husserl. This study uses interview and observation techniques for data collection. Data analysis techniques are data reduction that will process identifying, evaluating, and selecting data relevant to the research focus. This study discusses the direct experiences of cattle farmers, such as being unprepared to face FMD outbreaks, some even becoming ill due to thoughts of their livestock. Cattle farming is an inseparable part of the daily lives of people in Trenggalek Regency, as it is both a primary source of income and a source of secondary income with high economic value. Thus, this study explores the experiences of cattle farmers during the outbreak.